MDM2 as a Rational Target for Intervention in CDK4/6 Inhibitor Resistant, Hormone Receptor Positive Breast Cancer - Portman, Neil; Chen, Julia; Lim, Elgene (Frontiers in Oncology, 2021)
With the adoption of inhibitors of cyclin dependent kinases 4 and 6 (CDK4/6i) in combination with endocrine therapy as standard of care for the treatment of advanced and metastatic estrogen receptor positive (ER+) breast cancer, the search is now on for novel therapeutic options to manage the disease after the inevitable development of resistance to CDK4/6i. In this review we will consider the integral role that the p53/MDM2 axis plays in the interactions between CDK4/6, ERα, and inhibitors of these molecules, the current preclinical evidence for the efficacy of MDM2 inhibitors in ER+ breast cancer, and discuss the possibility of targeting the p53/MDM2 via inhibition of MDM2 in the CDK4/6i resistance setting.